La dictadura en la República romana clásica como referente paradigmático del régimen de excepción constitucional - Siles Vallejos, Abraham (2014)
The starting point of the article is the idea that the original model of state of emergency government established to save the Constitution can be found in the Classical Roman Republic. It makes the characteristics of this institution to be analyzed. Institution that has founded an intellectual ‘tradition’ in the political and legal Western thought. The study also comments the characteristics that distinguish the “Roman dictatorship” as a concept that lightens the theoretical options of people who worry about the constitutional emergencies and the powers to set against.